The Effect of Lecturers’ Mental Workload and Job Satisfaction on Work Life Balance - Mensah, S. (University of Ghana, 2016)
Due to the nature of the work of University lecturers’ they are likely to experience high mental workload and varied behavioral outcomes such as job satisfaction. These conditions may invariably affect how well they will be able to balance their work and personal lives concurrently. Notwithstanding these causal relationships, the working conditions of lecturers’ can influence their work-life balance. As such, the purpose of this study was to assess the effect of University lecturers’ mental workload and job satisfaction on their work-life balance. The study adopted a quantitative approach and sampled 312 University lecturers from the University of Ghana, Accra. Statistical Package for Social Science (SPSS) version 22 was the main statistical tool used. Data was analysed by way of descriptive, correlation and simple linear regression. The findings indicate that mental workload has no effect on lecturers’ work-life balance. Job satisfaction on the other hand had a negative effect on work-life balance. As a result of these findings, it is recommended that University authorities should adopt work life balance policies to assist lecturers cope with their work and family lives whiles enjoying their work.
Thesis (MPhil)
Keywords: Lecturer; Mental Workload; Job Satisfaction; Work Life Balance; Ghana